IN SILICO STUDY OF ETHYL P-METHOXYCINNAMATE (EPMS) AND GALANGIN COMPOUND AGAINTS NON-STRUCTURAL PROTEIN 3 (6W6Y) AND NON-STRUCTURAL PROTEIN 5 (6M2N) AS POTENTIAL ANTI-SARS CoV-2 DRUG - Achmad Tri Sugiarto Kharisul Islam Fazri; Prof. Dr. Apt. Roihatul Mutiah, M.Kes; dr. Dewi Santosaningsih, MKes, SpMK, PhD; Ike Prafita Sari (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Coronavirus Disease 2019 or Covid-19 is an acute respiratory infection caused by the Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS-CoV-2) which causes a pandemic in various parts of the world. Studies in silico of natural compounds reveal potential drug candidate. Objective: This research aims to predict the binding affinity of Etil P-Metoksi Sinamat (EPMS) and Galangin to Non-Structural Protein 3 (NSP3) and Non-Structural Protein 5 (NSP5) receptors using insilico approach. Methods: This study using EPMS and Galangin against NSP3 and NSP5 of SARS CoV-2 while Remdesivir used as reference drug. Ligand interaction predicted using Molegro Virtual Docker 6.0. Physicochemical properties predicted using SwissADME. Prediction of ligand toxicity was evaluated using Protox II Online Tool and pkCSM online tool base on LD50 classification. Results: EPMS compound had the best affinity and had the most stable binding on NSP3 (Rerank score -130.11 kcal/mol, H-Bond -10.10 kcal/mol, Moldock Score -140.56 kcal/mol) and NSP5 (Rerank score -113.87 kcal/mol, H-Bond -10.19 kcal/mol, Moldock Score -117.29 kcal/mol). Galangin compounds have lower affinity for NSP3 (Rerank score -107.02 kcal/mol, H-Bond -7.61 kcal/mol, Moldock Score -103.75 kcal/mol) and NSP5 (Rerank score -84.40 kcal/mol H-Bond -9.88 kcal/mol,Moldock Score -100.53 kcal/mol). The Docking of these two compounds were better when compared to Remdesivir in NSP3 (Rerank score -83.55 kcal/mol, H-Bond -6.88 kcal/mol, Moldock Score -99.86 kcal/mol) and NSP5 (Rerank score -83.55 kcal/mol, H-Bond -3.80 kcal/mol, Moldock Score -100.45 kcal/mol). Galangin and EPMS compounds to have better oral bioavailability than Remdesivir compounds. In the toxicity prediction test, the results showed that the EPMS compound was included in class 6 with an LD50 of 7900 mg/kg, Galangin compound was included in class 5 with an LD50 of 3919 mg/kg, Remdesivir compound was included in class 4 with an LD50 of 1190 mg/kg. Conclusion: EPMS reveal best affinity, bioavaibility and toxicity with NSP3 and NSP5.